ANALISIS FAKTOR-FAKTOR BALANCED SCORECARD (BSD) TERHADAP OPTIMALISASI PERSPEKTIF KINERJA KEUANGAN - Zulmita, Zulmita; Wibawa, Herry Wira; Paryanti, Atik Budi (Feb Universitas Dirgantara Marsekal Suryadarma, 2021)
In this global era, companies are demanded by consumers for all kinds of good quality products, services and prices, etc., in order to meet customer satisfaction. Companies in meeting these qualities need to formulate a good total performance, not only financial-related but also non-financial performance. The analytical method used is descriptive qualitative and statistical methods using multiple linear regression analysis tools, simultaneous significance testing and partial significance testing. Data collection was carried out by distributing questionnaires to 5 companies with 105 respondents consisting of 25 customers and 80 employees. All respondents are saturated samples with nonprobability sampling technique. The results showed that the Financial Perspective variable t count value is 6.28> t-table (1.96397), the significant level is 0.000> 0.05, so the Financial Perspective has a significant effect on the Optimization of Financial Performance Perspectives, the Customer Perspective variable, the t value is 3, 25> t-table (1.96397), a significant level of 0.042> 0.05, then the Financial Perspective has a significant effect on the Optimization of Financial Performance Perspectives, the Internal Business Perspective variable t-value is 4.239> t-table (1.96397), a significant level of 0 , 12> 0.05, the Internal Business Perspective has a significant effect on the Optimization of Financial Performance Perspectives, the Growth and Development Perspective variable, the t value is 4.453> t-table (1.96397), the significant level is 0.019> 0.05, so the Growth and Development Perspective has a significant effect. on Optimizing Financial Performance Perspectives.Â Keywords: Financial Perspective, Customer Perspective, Internal Business Perspective, Learning and Growth Perspective, Optimizing Financial Performance Perspective.